The Role of Endogenous Beta-Endorphin and Enkephalins in the Crosstalk Between Ethanol and Morphine - Andy Tseng; Syed Muzzammil Ahmad; Abdul Hamid; Kabirullah Lutfy (Pharmaceuticals)
Background: There is clinical concern about the combined use of alcohol and opiates. Several lines of evidence support an interaction between alcohol and the endogenous opioid system. Thus, we hypothesized that ethanol, by causing the release of opioid peptides, may sensitize the system to the action of exogenous opioids such as morphine. Objectives: In this study, using the place conditioning paradigm, a model of reward, we determined whether a morphine challenge would alter the pre-established preference induced by ethanol conditioning in mice, and whether this response was mediated by the mu opioid receptor (MOP). Given that ethanol exposure stimulates the release of opioid peptides, we also assessed the role of beta-endorphin (β-END) and enkephalins (ENKs) in this response. Methods: Mice lacking MOPs, β-END, and/or ENKs, and their respective wild-type controls were tested for preconditioning place preference on day 1. Mice were then conditioned with ethanol (2 g/kg) versus saline on days 2 to 4 and then tested under a drug-free state for postconditioning place preference on day 5. On day 8, mice received a single injection of morphine (5 mg/kg) and were tested for place preference. On the test days, mice were placed in the central chamber and allowed to explore the chambers. The amount of time that mice spent in the drug-paired chamber was recorded. Results: We found that a challenge dose of morphine given on day 8 enhanced the conditioned place preference (CPP) response in mice previously conditioned with ethanol. This response was abolished in MOP-null mice, confirming the role of MOPs in this response. Although this enhanced response was not altered in mice lacking either β-END or ENKs compared to their wild-type littermates/controls, it was completely blunted in mice lacking both β-END and enkephalins. Conclusions: Together, these results suggest that these opioid peptides jointly mediate the crosstalk between the rewarding actions of morphine and ethanol.